A literature review of liver function test elevations in rifampin drug–drug interaction studies - Ibrahim, Sherry M.; Pithavala, Yazdi K.; Vourvahis, Manoli; Chen, Joseph (Clinical and translational science, 2022)
Although rifampin drug–drug interaction (DDI) studies are routinely conducted, there have been instances of liver function test (LFT) elevations, warranting further evaluation. A literature review was conducted to identify studies in which combination with rifampin resulted in hepatic events and evaluate any similarities. Over 600 s and manuscripts describing rifampin DDI studies were first evaluated, of which 30 clinical studies reported LFT elevations. Out of these, 11 studies included ritonavir in combination with other drug(s) in the rifampin DDI study. The number of subjects that were discontinued from treatment on these studies ranged from 0 to 71 (0–100% of subjects in each study). The number of subjects hospitalized for adverse events in these studies ranged from 0 to 41 (0–83.67% of subjects in each study). LFT elevations in greater than 50% of subjects were noted during the concomitant administration of rifampin with ritonavir‐boosted protease inhibitors and with lorlatinib; with labeled contraindication due to observed hepatotoxicity related safety findings only for saquinavir/ritonavir and lorlatinib. In the lorlatinib and ritonavir DDI studies, considerable LFT elevations were observed rapidly, typically within 24–72 h following co‐administration. A possible sequence effect has been speculated, where rifampin induction prior to administration of the combination may be associated with increased severity of the LFT elevations. The potential role of rifampin in the metabolic activation of certain drugs into metabolites with hepatic effects needs to be taken into consideration when conducting rifampin DDI studies, particularly those for which the metabolic profiles are not fully elucidated.